First record of Japanese sea cucumber Apostichopus japonicus (Selenka, 1867) (Aspidochirotida: Stichopodidae) from the Mediterranean Sea, Turkey - Tolon, Mustafa Tolga; Gökçek, Emel Özcan (Zootaxa, 2025)
The Japanese sea cucumber Apostichopus japonicus (Selenka, 1867), native to the East Asian coasts, was recorded for the first time in the Mediterranean Sea along the east Aegean coast (Izmir, Turkey). Fifty-eight specimens were collected by scuba diving at depths up to 10 m between July and August 2024. Species identity was confirmed by morphological examination and molecular analyses using partial regions of the cytochrome oxidase subunit I (COI) and 16S ribosomal RNA (16S rRNA) genes. Phylogenetic analyses based on COI and 16S rRNA sequences confirmed species identity, with haplotypes closely matching those of A. japonicus from its native range. Specimens ranged from 72.5 to 160.0 mm in total length and 21.79 to 88.30 g in gutted body weight, with a slightly negative allometric growth pattern (b = 1.821). Examination of ossicles, including reduced tables, rods, and elongated button-like structures on the body wall and papillae, confirmed the specimens as A. japonicus. The presence of mature individuals and a high proportion of juveniles suggests successful reproduction and establishment in this region. The abiotic data indicated that the environmental conditions at the sampling site were within the tolerance range. This study documented the first occurrence of A. japonicus in the Mediterranean Sea, highlighting its potential to expand its range and to adapt to new environments.